Computational Fluid Dynamic Analysis at Dam Spillway Due to Different Upstream Water Levels - Hassan N.H.; Kamarulbahrin S.Z.A.S.; Zawawi M.H.; Mazlan A.Z.A.; Abas M.A.; Zainol M.R.R.M.A.; Kamaruddin M.A. (Springer Science and Business Media Deutschland GmbH, 2025)
This paper analyses the fluid dynamic on the dam spillway structure when the water spilling event occurred. The parameters determined in this study are velocity and pressure. A 3D Computational Fluid Dynamics (CFD) model of the dam spillway structure and the fluid boundary condition was developed using FLUENT. The result of the CFD model shows that hydrostatic pressure for all water levels was observed at the upstream section. The highest velocity and pressure occur at the highest water level which are 3.2m/s and 1.526MPa, respectively, at the spillway wall. High water velocity may contribute to critical stress due to the high pressure. All of the cases from 146 to 153m water level show the fluid flows which are at reasonable velocity and pressure at the spillway. However, the continuous interaction with water towards the granite may affect the scouring effect of the granite in the long-term run. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd 2024.